SARS-CoV-2 Infection and Antibody Seroprevalence among UK Healthcare Professionals Working with Cancer Patients during the First Wave of the COVID-19 Pandemic. Issue 10 (October 2021) - Favara, D.M.; McAdam, K.; Cooke, A.; Bordessa-Kelly, A.; Budriunaite, I.; Bossingham, S.; Houghton, S.; Doffinger, R.; Ainsworth, N.; Corrie, P.G.
Abstract: Aims: The proportion of UK oncology healthcare professionals (HCPs) infected with SARS-CoV-2 during the COVID-19 pandemic's first wave is unknown. The primary aim of this study was to determine the SARS-CoV-2 infection and seroprevalence rates among HCPs. Materials and methods: Patient-facing oncology HCPs working at three large UK hospitals during the COVID-19 pandemic's first wave underwent polymerase chain reaction (PCR) and antibody testing [Luminex and point-of-care (POC) tests] on two occasions 28 days apart (June–July 2020). Results: In total, 434 HCPs were recruited: nurses (58.3%), doctors (21.2%), radiographers (10.4%), administrators (10.1%); 26.3% reported prior symptoms suggestive of SARS-CoV-2. All participants were PCR negative during the study, but 18.4% were Luminex seropositive on day 1, of whom 42.5% were POC seropositive. Nurses had the highest seropositive prevalence trend (21.3%, P = 0.2). Thirty-eight per cent of seropositive HCPs reported previous SARS-CoV-2 symptoms: 1.9 times higher odds than seronegative HCPs ( P = 0.01). Of 400 participants retested on day 28, 13.3% were Luminex seropositive (92.5% previously, 7.5% newly). Thirty-two per cent of initially seropositive HCPs were seronegative on day 28. Conclusion: In this large cohort of PCR-negative patient-facing oncology HCPs, almost one in five were SARS-CoV-2 antibody positive at the start of the pandemic's first wave. Our findings that one in three seropositive HCPs retested 28 days later became seronegative support regular SARS-CoV-2 PCR and antibody testing until widespread immunity is achieved by effective vaccination. Highlights: In a large cohort of PCR-negative oncology healthcare professionals (HCPs) ( n = 434) almost one in five were SARS-CoV-2 antibody positive at the start of June 2020, suggesting prior SARS-CoV-2 infection during the first wave of the COVID-19 pandemic. 47.5% of these had antibodies to both nucleocapsid (N) and surface (S) antigens, whereas 40% had antibodies only to the N antigen and 12.5% had antibodies only to the S antigen. HCPs who described previous symptoms consistent with COVID-19 were twice as likely to be SARS-CoV-2 seropositive compared with asymptomatic HCPs. Nearly one third of seropositive HCPs became seronegative after 4 weeks, all of whom were previously asymptomatic and were previously reactive to the N antigen only ( P < 0.0001). Nurses were the HCP group with the highest seroprevalence rates at both time points.